THE USE OF SNOWBALL THROWING MODEL IN LEARNING AT MA QURRATUL UYUN PAMEKASAN - Mohammad Salehoddin; Moh. Badrus Syamsi (Universitas Madura, 2020)
This study aims to investigate the ways teachers of MA Qurratul Uyun implementing snowball throwing in learning as well as their obstacles in implementing it. This research uses qualitative by using descriptive approach. The participants of this study are the teachers at MA Qurratul Uyun. The data are obtained through observation, interview, and documentation. The result shows that teachers give the students materials and make groups as well call one of the students in each group to give clarification about items. Each leader of group take one ball and text, then return to each group and explain the material which the teacher has explained to his or her friends. Each cluster takes a text in ball and make a question based on text, after that they throw to another groups. Then, the teachers give chances to the students to answer the question, and the last the teacher offer conclusion based on the student’s respond. The problem of the teachers is the students are getting lazy to read of the text. Therefore, it is important for the teachers to select appropriate text to increase their motivation in learning. This kind of model is an alternative solution to provide effective learning to the students.